Phytochemical Constituents of Cinnamomum burmannii (Ness & T.Nees) Blume: A Systematic Review - Sultan Rahwal; Yoki Permana Agung; Suci Indah Ramadani; Friardi Ismed; Nurwahidatul Arifa (Universitas Labuhanbatu, 2025)
Background: Cinnamomum burmannii is an Indonesian native cinnamon species with significant potential for developing pharmaceutical and functional food products. Methodology: This study aims to identify and analyze the phytochemical constituents of C. Burmannii through a systematic literature review using PRISMA databases such as PubMed, Scopus, and Science Direct,were searched from 2015-2025. Findings: The findings reveal that C. Burmannii contains diverse bioactive compounds, including aromatic aldehydes, phenolics, flavonoids, terpenoids, coumarins, aromatic alcohols, organic acids, and aromatic esters. Dominant compounds such as cinnamaldehyde, quercetin, catechin, and eugenol exhibit strong antimicrobial, antioxidant, antidiabetic, anti-inflammatory, and analgesic activities. Quantitative analysis shows total phenolic content ranging from 31–89 mg GAE/100 g, total flavonoid 15–80 mg QE/100 g, and total tannin 89–217 mg CE/g, with ethanol extraction yielding optimal results. Several novel pure compounds, including Burmanoside, Burmafuranic acid, Burmannic acid, and o-hydroxycinnamic acid, have been isolated and demonstrate antiproliferative and photoprotective activities. Contribution: This systematic review highlights the diversity of phytochemical constituents in C. Burmannii and emphasizes the influence of plants parts and extraction methods on phytochemicals profiles.